CRM ASSESSMENT FOR PREPARING THE AIR TRANSPORTATION BUSINESS FOR A POST-PANDEMIC FUTURE - Rafie, Irfan; Rahmiati, Filda (UNIVERSITAS PAKUAN, 2021)
This paper examined the impact of customer relationship management (CRM) elements on customer satisfaction and loyalty. CRM is an airline strategy for individualizing its service, creating better communication channels with customers, and ensuring customer satisfaction on loyalty. Four essential elements of CRM measured in this study: service quality, price fairness, perceived safety, and social media marketing. The study employed a quantitative approach and base on 178 respondents. Partial Least Square Structural Equation Model (PLS-SEM) is used to examine the variables relationship. The finding shows that the respondents response is significantly related and contributes to customer satisfaction and loyalty expect for price fairness. By giving more discounts or promotions creates attention to the customer.